Purification and characterization of Clostridium sordellii lethal toxin and cross-reactivity with Clostridium difficile cytotoxin. - Popoff, M R (1987)
Lethal toxin (LT) was purified from Clostridium sordellii IP82 by DEAE-Trisacryl, Ultrogel AcA3-4 gel filtration, and hydroxyapatite column chromatography. The molecular weight of purified LT was estimated to be 240,000 to 250,000, and the pI was at pH 4.55. LT was lethal for mice by intraperitoneal injection (3.4 X 10(5) mouse lethal doses per mg of protein), cytotoxic for Vero cells (6.1 X 10(4) cytotoxic units per mg of protein), erythematous and edematous by intradermal injection in guinea pigs, and induced a moderate fluid accumulation in the guinea pig intestinal loop test. The lethal activity was inactivated by N-bromosuccinimide, N-chlorosuccinimide, chloramine-T, and sodium dodecyl sulfate. The data suggest that tryptophan and methionine residues present in the toxin are important for lethal activity. Furthermore, LT was inactivated by oxidized glutathione and activated by dithiothreitol. Inactivation by sulfhydryl-group reagents 5,5'-dithiobis(2-nitrobenzoic acid) and iodoacetamide was only obtained with dithiothreitol-treated LT. Thiol groups which are protected as a disulfide bond(s) seem to be essential for the LT activity. A specific antiserum against LT neutralized the biological activities of LT and also cytotoxic activity and lethal activity of Clostridium difficile toxin B but not of C. difficile toxin A. However, this serum did not recognize antigen from C. difficile culture supernatant by immunoblotting. It was concluded that antibodies prepared from C. sordellii LT that neutralized C. difficile cytotoxic activity recognized a low number of epitopes or tertiary structures of C. difficile cytotoxin.